New record and range extension of the roughskin spurdog Cirrhigaleus asper in the Caribbean Sea - Polanco-Vásquez, Francisco; Hacohen-Domené, Ana; Becerril-García, Edgar E.; Hernández, Sebastián (Revista de Biología Marina y Oceanografía, 2022)
This study constitutes the first record and a range extension of the roughskin spurdog (Cirrhigaleus asper) in the Caribbean Sea. A total of three mature female specimens were captured by artisanal fishermen between March and May of 2016 in the coastal community of El Quetzalito, Izabal, Guatemala. The total length of the sharks ranged from 1,110-1,280 mm, which is the largest total length so far reported for this species.